Tumor of follicular infundibulum with unique features - Natalie Haddad; Jayme de Oliveira Filho; Mariana Junqueira Lacerda Reis; Alexandre Ozores Michalany; Kassila da Rosa Nasser; Ana Maria França Corbett (Sociedade Brasileira de Dermatologia, 2014)
Tumor of the follicular infundibulum is a rare benign cutaneous adnexal neoplasm with variable clinical presentation. In most cases the diagnosis is made with the help of histopathology, due to lack of a characteristic clinical presentation. The most common form is a solitary lesion, but it can be multiple or eruptive, then called infundibulomatose. This case report illustrates a patient with multiple lesions of tumor of the follicular infundibulum with bizarre aspect and atypical location.